2023
DOI: 10.1093/molbev/msad241
|View full text |Cite
|
Sign up to set email alerts
|

Opsin Gene Duplication in Lepidoptera: Retrotransposition, Sex Linkage, and Gene Expression

Peter O Mulhair,
Liam Crowley,
Douglas H Boyes
et al.

Abstract: Color vision in insects is determined by signaling cascades, central to which are opsin proteins, resulting in sensitivity to light at different wavelengths. In certain insect groups, lineage-specific evolution of opsin genes, in terms of copy number, shifts in expression patterns, and functional amino acid substitutions, has resulted in changes in color vision with subsequent behavioral and niche adaptations. Lepidoptera are a fascinating model to address whether evolutionary change in opsin content and seque… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 93 publications
2
7
0
Order By: Relevance
“…We discovered variety in the number of opsin genes across species, particularly in the LW and SW opsins. Our results suggest that caddisflies have evolved a diverse range of opsins, likely driven by life history strategies and ambient light conditions as has been hypothesized in other insect orders (Briscoe et al, 2010;Feuda et al, 2016;French et al, 2015, Futahashi et al, 2015Guignard et al, 2022;Lord et al, 2016;Mulhair et al, 2023;Sharkey et al, 2017;Sondhi et al, 2021;Suvorov et al, 2017).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…We discovered variety in the number of opsin genes across species, particularly in the LW and SW opsins. Our results suggest that caddisflies have evolved a diverse range of opsins, likely driven by life history strategies and ambient light conditions as has been hypothesized in other insect orders (Briscoe et al, 2010;Feuda et al, 2016;French et al, 2015, Futahashi et al, 2015Guignard et al, 2022;Lord et al, 2016;Mulhair et al, 2023;Sharkey et al, 2017;Sondhi et al, 2021;Suvorov et al, 2017).…”
Section: Discussionsupporting
confidence: 67%
“…Opsin evolution has been more thoroughly studied in Lepidoptera, the sister order to Trichoptera (Briscoe et al, 2010; Feuda et al, 2016; Finkbeiner & Briscoe, 2021; Frentiu et al, 2007; Guignard et al, 2022; Macias-Muñoz et al, 2019; Mulhair et al, 2023; Sison-Mangus et al, 2006; 2008; Sondhi et al, 2021; Spaethe & Briscoe, 2004). Recent work has identified several instances of family– and species-specific duplications of visual opsin genes, many of which have resulted in adaptations that extend visual capacity (Frentiu et al, 2007; Mulhair et al, 2023; Sison-Mangus et al, 2006; 2008). For example, butterflies in the family Lycaenidae use both a green-shifted SW opsin and a red-shifted LW opsin to better discriminate different wavelengths (Liénard et al, 2021; Sison-Mangus et al, 2006; 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used RELAX to test for relaxation and intensification of selection on the significant partitions identified by CmC. This method has successfully been applied to test for relaxed selection on opsin genes in several lineages including cichlids, bats, butterflies, and mirid bugs ( Gutierrez et al 2018a , 2018b ; Hauser et al 2021 ; Xu et al 2021 ; Mulhair et al 2023 ). The HYPHY models each automatically inferred gene trees with the GTR model, which were rerooted on Ascaphus truei prior to analyses.…”
Section: Methodsmentioning
confidence: 99%
“…(B) Connections between lamina monopolar cells (L1-L5) in adjacent lamina cartridges in D. melanogaster and the parasitoid wasp Megaphragma viggianii. [1] repertoires and their expression underlies differences in spectral sensitivities, color vision, and motion detection within and among insect species [15][16][17][18] (Box 2). For example, it was recently shown that sexlinkage of UVRh1 underlies differential UV sensitivity between male and female Heliconius butterflies.…”
Section: Superposition Eyesmentioning
confidence: 99%